Genetic diversity of wedgefishes and guitarfishes at landing sites in east Indonesia using Cytochrome Subunit I (COI) - MARYROSE EASTER TAPILATU; DIAH PERMATA WIJAYANTI; SUBAGIYO SUBAGIYO; ANDRIANUS SEMBIRING; NI LUH ASTRIA YUSMALINDA; ENEX YUNIARTI NINGSIH; MUHAMMAD DANIE AL MALIK; NI PUTU DIAN PERTIWI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Tapilatu ME, Wijayanti DP, Subagiyo, Sembiring A, Yusmalinda NLA, NIngsih EY, Malik MDA, Pertiwi NPD. 2023. Genetic diversity of wedgefishes and guitarfishes at landing sites in east Indonesia using Cytochrome Subunit I (COI). Biodiversitas 24: 3120-3127. Wedgefish and guitarfish are considered endangered and protected by law in Indonesia due to pressure from overexploitation. They are highly exploited because of their economic value. This condition impacts the decline in the number of populations to the value of genetic diversity. This study used mitochondrial DNA to assess the genetic diversity of wedgefishes and guitarfishes which landed in the eastern part of Indonesia. We found Rhynchobatus australiae (Whitley, 1939) to be the most common species (14 out of 26 sequenced samples), with Glaucostegus typus (Bennett, 1830) and Rhinobatos jimbaranensis (Last, White, & Fahmi, 2006) appearing infrequently. COI sequences were obtained from the NCBI database and utilized in the study to compare population differentiation. Among the R. australiae populations, the results showed that the genetic diversity (Hd) values from Papua, Bali, and Lombok were 1.00, 0.67, and 0.75, respectively. In Papua, G.typus populations showed genetic diversity values of 0.90. R. jimbaranensis from Bali showed a genetic diversity of 0.50. Papua populations indicated higher genetic diversity than Bali and Lombok populations. Furthermore, the analyses of pairwise FST values and AMOVA indicated moderate genetic divergence across reference populations of R. australiae and G. typus in this study. Based on this value, a cautious conservation strategy in optimizing fisheries management will be required to limit anthropogenic impacts.